An Aspiration Adaptation Based Model of the Timing of Product Innovation - Sabine Pittnauer; Martin Hohnisch; Dietrich Stauffer (University of Bonn, Bonn Graduate School of Economics (BGSE), 2003)
This paper applies the theory of aspiration adaptation to industrial economics. It is motivated by the question, frequently raised in the context of theoretical and empirical research on industrial innovation, of what triggers a firm's innovative activity. We develop a model of the management's decision-making relating a firm's competitive behavior, in particular the decision to start the development of a new product generation, to the current and past values of the firm's growth rate and profitability. This linkage offers an alternative perspective on the incentives for innovation. Furthermore, we explore the relationship between firm size and innovativeness resulting from our model.
Keywords: L11; D21; O31; L25; L21; 330; Aspiration Adaption; Bounded Rationality; Product Innovation; Innovation; Betriebliche Terminplanung; Betriebswirtschaftliches Ziel; Beschränkte Rationalität; Erwartungstheorie; Industrieökonomik; Evolutionsökonomik; Theorie